The instability of female construction as reflected in novel Hati Seorang Perempuan - Adawiyah, Robiatul; Pujiharto (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
The evolving and persistent gender constructs in society have greatly disadvantaged women, placing them in a subordinate position and limiting their choices in life. These negative impacts have prompted women to rise and fight for gender equality, a struggle not only in the real world but also in fictional works such as Maria A. Sardjono's novel Hati Seorang Perempuan. This novel features an independent female protagonist who upholds women's self-esteem and rejects the gender construction system imposed by society. In contrast, the male protagonist in this novel is portrayed as a figure who highly upholds the gender construction system in a society steeped in patriarchy. However, the gender construction believed by the female and male protagonists in the novel is not absolute but full of instability. Therefore, this study aims to identify the instability of female and male constructions in the novel HSP. Based on the analysis, it was found that the strong, independent female character that does not care about society's views, as formed by the female protagonist in the novel HSP, cannot completely break free from society's perspective, the biological need to love and be loved, and self-fragility. A similar phenomenon occurs in the male protagonist, where the construction of men as selfish and placing women in a subordinate position, as portrayed by the male protagonist in the novel HSP, is ultimately not fixed and is full of instability, as seen in the male protagonist's logocentric opposition.